16a+37a+6=12

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

(16a+3)⋅2=(7a+6)⋅1

Simplify (16a+3)⋅2.

Apply the distributive property.

16a⋅2+3⋅2=(7a+6)⋅1

Multiply.

Multiply 2 by 16.

32a+3⋅2=(7a+6)⋅1

Multiply 3 by 2.

32a+6=(7a+6)⋅1

32a+6=(7a+6)⋅1

32a+6=(7a+6)⋅1

Multiply 7a+6 by 1.

32a+6=7a+6

Move all terms containing a to the left side of the equation.

Subtract 7a from both sides of the equation.

32a+6-7a=6

Subtract 7a from 32a.

25a+6=6

25a+6=6

Move all terms not containing a to the right side of the equation.

Subtract 6 from both sides of the equation.

25a=6-6

Subtract 6 from 6.

25a=0

25a=0

Divide each term by 25 and simplify.

Divide each term in 25a=0 by 25.

25a25=025

Cancel the common factor of 25.

Cancel the common factor.

25a25=025

Divide a by 1.

a=025

a=025

Divide 0 by 25.

a=0

a=0

a=0

Solve for a (16a+3)/(7a+6)=1/2